Debt Management Performance Assessment : Maldives - World Bank (Washington, DC, 2013)
From October 19 to 27, 2009, a World Bank team in collaboration with the Commonwealth Secretariat undertook a debt management performance assessment of the Government of the Republic of Maldives (GRM). The objective was to undertake a comprehensive assessment of debt management functions using the Debt Management Performance Assessment tool (DeMPA), version of November 2008. As part of the assessment, the team met relevant officials dealing with public debt management in Maldives from the Ministry of Finance and Treasury (MOFT), the Maldives Monetary Authority (MMA), the Attorney General, the Auditor General's office, the National Disaster Management Centre, Capital Markets Development Authority, the State Bank of India and the Bank of Maldives. The assessment for Maldives was timely. The current situation shows moderately high government debt levels (around 55 percent of GDP) with sustainability indicators reflecting vulnerabilities (at current trajectory of primary deficit, the International Monetary Fund (IMF) article four report estimated debt levels would reach 75 percent of GDP by 2013). The recently concluded Public Expenditure and Financial Accountability (PEFA) findings highlighted areas for improvement relating to budget execution and credibility, audit and legislative oversight, cash management and the Treasury Single Account (TSA), and monitoring and managing fiscal risks.